Structural investigations along a low-angle normal fault zone (Kythnos, Greece) - Lenauer, I.; Mörtl, G.; Grasemann, B.; Iglseder, C. (TRABAJOS DE GEOLOGÍA, 2009)
Recent field investigations have revealed a high-strain zone in the south of Kythnos (Greece). Massive layers of ultrafine-grained Mn-rich calcitic mylonitic marbles and several generations of cataclasites hint at a high-strain event in the crust and are associated with a low-angle shear zone. We investigate fold-fault-relationships and deformation events preceding and post-dating normal faulting and compare the tectono-metamorphic history with adjacent islands in the Western Cyclades.